The analysis of regulatory DNA : current developments, knowledge and applications uncovering gene regulation - Berendzen, Kenneth W.; Kilian, Joachim; Wanke, Dierk (Bentham Science Publishers, 2013)
This e-book provides a resource for summarizing current knowledge eukaryotic transcription and explores cis-elements and methods for their analysis, prediction and discovery. The book also presents an overview of exploring gene regulatory networks, chromatin, and miRNAs. Information about state-of-the-art techniques for the determination of TF - cis-element interactions in vivo and in silico give cutting edge insights on how genomic-scale research is being approached.